Seafood as functional food - Soccol,Marcilene C. Heidmann (2003)
Functional food presents specific physiological properties, supplies nutrients and can be naturally found in formulated food or added to it. Seafood plays an important role in human diet, representing the largest stock available of w-3 polyunsaturated fatty acids, especially eicosapentaenoic (EPA) and docosahexaenoic (DHA). Scientific researchers have intensified their studies on fatty acids due to their importance in preventing and/or curing diseases, especially cardiovascular and inflammatory ones. This review describes the most important aspects of w-3 fatty acids found in fish, as well as their roles in the mechanism involved in the prevention and control of diseases.